Gut-derived Faecalibaculum rodentium exerts anti-cancer effects on colorectal cancer by modulating PDPN-CLEC-2 signaling pathway - Xiaojuan Yang; Miao Liu; Ting Wang; Xinjuan Ma; Zhirong Guan; Bin Ma; Xiangguo Duan; Chunxia Su (mSystems)
ABSTRACT Dynamic changes in microbial composition are related to the progression of colorectal cancer (CRC); however, specific microbes with anti-CRC properties have not been identified. Here, we aimed to determine the effect of Faecalibaculum rodentium on CRC progression. In this study, the effect of F. rodentium was assessed in an azoxymethane (AOM)/dextran sulfate sodium salt (DSS)-induced CRC mouse model as well as in human CRC cell lines. Changes in anti-tumor immune responses were evaluated by flow cytometry. The functional metabolites produced by F. rodentium were identified by gas chromatography‒mass spectrometry (GC‒MS). The subcutaneously injected BALB/c mice with CT26 CRC cells were used to evaluate the effect of acetate produced by F. rodentium. We found that supplementation with F. rodentium suppressed CRC in an AOM/DSS-induced CRC mouse model as well as in the human CRC cell lines SW620 and HT-29. GC‒MS revealed that acetate is a functional tumor-suppressive metabolite produced by F. rodentium, and the tumor volume and tumor weight in the CRC model were inhibited by acetate administration. Mechanistically, F. rodentium produced acetate, which suppressed the expression of PDPN on CD8+ T cells and that of C-type lectin-like receptor 2 (CLEC-2) on tumor cells. As a consequence, CD8+ T-cell immunity was increased both in vivo and in vitro. In addition, we revealed that the acetate produced by F. rodentium can modulate podoplanin (PDPN)/CLEC-2/PI3K/AKT/mTOR signaling in CRC. In summary, F. rodentium produced acetate inhibits CRC by promoting CD8+ T-cell immunity and modulating the PDPN-CLEC-2 pathway. Our data indicate that F. rodentium is a potential probiotic for cancer prevention and treatment.IMPORTANCEThis study identified Faecalibaculum rodentium as a novel probiotic that suppresses colorectal cancer (CRC) via acetate, which enhances CD8+ T-cell immunity by blocking PDPN-CLEC-2 and induces tumor cell apoptosis through PI3K/AKT/mTOR pathway. These findings validated F. rodentium and acetate as dual-action therapeutic candidates through immune response activation and intrinsic tumor targeting by murine models and human CRC cell lines, thereby providing innovative strategies for CRC treatment.